Targeting DNA-Protein Crosslinks via Post-Translational Modifications - Leng, Xueyuan; Duxin, Julien P. (Frontiers in Molecular Biosciences, 2022)
Covalent binding of proteins to DNA forms DNA-protein crosslinks (DPCs), which represent cytotoxic DNA lesions that interfere with essential processes such as DNA replication and transcription. Cells possess different enzymatic activities to counteract DPCs. These include enzymes that degrade the adducted proteins, resolve the crosslinks, or incise the DNA to remove the crosslinked proteins. An important question is how DPCs are sensed and targeted for removal via the most suited pathway. Recent advances have shown the inherent role of DNA replication in triggering DPC removal via proteolysis. However, DPCs are also efficiently sensed and removed in the absence of DNA replication. In either scenario, post-translational modifications (PTMs) on DPCs play essential and versatile roles in orchestrating the repair routes. In this review, we summarize the current knowledge of the mechanisms that trigger DPC removal via PTMs, focusing on ubiquitylation, small ubiquitin-related modifier (SUMO) conjugation (SUMOylation), and poly(ADP-ribosyl)ation (PARylation). We also briefly discuss the current knowledge gaps and emerging hypotheses in the field.